Difference Analysis of Digital Marketing Implementation in Enterprises Performance: Balanced Scorecard Perspective - Slamet Slamet; Muhammad Maslukil Adhim; Ilya Azmala (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
This study aims to determine the differences in Micro, Small, and Medium Enterprises’ (MSMEs) performance before and after implementing digital marketing. The research paradigm was quantitative with primary data sources. Furthermore, the research instrument was a questionnaire designed to measure MSMEs' performance in the balanced scorecard perspective on customer and internal business processes. The number of samples totaled 107 respondents, and data were collected directly from MSMEs in Malang City. The determination of respondents involved a judgment sampling approach. Data analysis was mainly descriptive (categorization index) which also involved hypothesis testing (sample paired t-test). The results showed that there were significant differences in MSMEs' performance before and after implementing digital marketing. These differences were shown by the results of data analysis, in both descriptive and hypothesis testing.